Prove, pelo lema de Euclides, que o mdc(a,b) = mdc(a, a-b), sendo a não nulo
Soluções para a tarefa
Respondido por
0
a = 40
b = 10
m.d.c(40,10) = m.d.c[40;(40 - 10)]
4
40 | 10 |
0
m.d.c(40,10) = m.d.c(40,30) = 10
1 3
40 | 30 | 10 |
10 0
m.d.c(40,30) = 10
b = 10
m.d.c(40,10) = m.d.c[40;(40 - 10)]
4
40 | 10 |
0
m.d.c(40,10) = m.d.c(40,30) = 10
1 3
40 | 30 | 10 |
10 0
m.d.c(40,30) = 10
Perguntas interessantes
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Biologia,
11 meses atrás
Geografia,
1 ano atrás